USE OF LEARNING MONITORING SHEET BY STUDENT'S PARENTS DURING THE COVID-19 PANDEMIC IN CLASS IV SD INPRES 1 TOLAI - Ni Luh Dhian Indriani; I Ketut Kertayasa; Ni Made Mega Hariani (STAH Dharma Sentana Sulawesi Tengah, 2023)
The purpose of this study was to determine the results of the validity and effectiveness of learning monitoring sheets by parents during the COVID-19 pandemic in grade IV SD Inpres 1 Tolai. Determination of informants by purposive sampling. The methods used were observation, interviews, monitoring sheets, documentation, and tests. Based on the results of validity in the field of content 87.5% and validation in the field of language 84.38%, on very valid category. Monitoring sheets can be applied during the COVID-19 pandemic, because they can be an alternative for teachers and parents in supervising and controlling students during the learning process both online and offline. So the results of interviews with teachers and parents stated that the monitoring sheet was very effective in being used in the learning process during the COVID-19 pandemic.